2015
DOI: 10.1111/papr.12321
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Sinus Arrhythmia and its Association with Pain in Women with Fibromyalgia Syndrome

Abstract: The results of VHR indices during the supine position and the DBT women with FMS suggest impairment of neurocardiac integrity associated with pain and the impact of FMS on the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
(49 reference statements)
2
26
0
Order By: Relevance
“…The relation between anxiety-depression and cardiac events in patients with FMS has been addressed in a very few amount of the studies. Zamuner et al (15) indicated that disruption of neurocardiac integrity in patients with FMS have an impact on pain and quality of life. In a study where the relation between anxiety, depression and arrhythmia have been investigated in 59 patients diagnosed with FMS, higher anxiety-depression scores were obtained when compared to the control group, but its relation with arrhythmia has not been suggested (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between anxiety-depression and cardiac events in patients with FMS has been addressed in a very few amount of the studies. Zamuner et al (15) indicated that disruption of neurocardiac integrity in patients with FMS have an impact on pain and quality of life. In a study where the relation between anxiety, depression and arrhythmia have been investigated in 59 patients diagnosed with FMS, higher anxiety-depression scores were obtained when compared to the control group, but its relation with arrhythmia has not been suggested (11).…”
Section: Discussionmentioning
confidence: 99%
“…Sarıfakıoğlu et al (11) did not find any relation between arrhythmia and anxiety-depression, but reported that the risk of atrial fibrillation was increased in patients with FMS. However, Zamuner et al (15) reported that the disruption of neurocardiac integrity in FMS have an impact on pain and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Brennan 1 , R. Breen 2 , J. Ashton 2 , C. Edel 3 , C. Farrell 4 , D. Moore 1 , P. Kenny 5 , O. FitzGerald 6 . 1 Tallaght Hospital, Tallaght, Dublin 24; 2 Beaumont Hospital, Dublin; 3 Merlin Park, Galway; 4 RSCI; 5 Connolly Hospital, Blanchardstown; 6 …”
Section: Musculoskeletal Triage Services In Irelandmentioning
confidence: 99%
“…Background: Several studies have shown that autonomic dysfunction plays an important role in the fibromyalgia syndrome (FMS). [1][2][3] Recent studies have used the active standing test to assess the cardiovascular autonomic control responses to the orthostatic stimulus in several disorders, including FMS. 4 However, there are few studies correlating symptoms and clinical factors with cardiovascular autonomic dysfunction.…”
Section: St Vincents University Hospital Dublin Irelandmentioning
confidence: 99%
“…The cardiac baroreflex system plays an important role in mediating the inverse relationship between lower BP and higher pain, and inverse relationships have been observed between pain sensitivity and resting baroreceptor sensitivity …”
Section: Introductionmentioning
confidence: 99%